Assessing law enforcement officer skills in Crisis Intervention Team (CIT) research: developing and implementing standardized scenarios - Watson, Amy C.; Jackson, Elisabeth; Fu, En; Bruno, Ron; Comartin, Erin; Kamin, Don; Pope, Leah G.; Vega, Eduardo; Compton, Michael T. (Frontiers in Psychology, 2024)
This paper outlines the development of standardized scenarios used to assess the efficacy of Crisis Intervention Team (CIT) training in a randomized, controlled trial. The objective was to create scenarios that accurately simulate mental health crisis situations for law enforcement officers, ensuring that each scenario tests specific CIT skills relevant to real-world encounters. Our process involved building an interdisciplinary team and drawing from the knowledge and experience of professionals in law enforcement, mental health, and performance arts to design a set of scenarios that are both realistic and challenging. The scenarios were developed to represent mental health crises that officers frequently encounter, such as mania, psychosis with agitation, and depression with suicidality. Each scenario requires officers to demonstrate CIT-specific skills such as verbal de-escalation, empathy, and critical decision-making. Our structured approach to developing these scenarios provides a replicable model for future studies that aim to assess the real-world effectiveness of mental health training for law enforcement as well as other professional groups.